Analysis of Community Satisfaction with the Integrated Police Service Center at the East Kutai Police - Partawijaya, Sigit; Ngarawula, Bonaventura; Sapto Adi, Dodot (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Public services are activities carried out in the framework of fulfilling service needs in accordance with statutory regulations for every citizen and resident for administrative services provided by public service providers. Public service providers are any state administration institutions that can be in the form of corporations or independent institutions established under law for public service activities. This study aims to evaluate community satisfaction with the East Kutai Police Integrated Police Service Center and to determine the extent to which the implementation of job evaluation of officers at the East Kutai Police Integrated Service Center. The method used by the author in this study is qualitative analysis supported by quantitative data. Qualitative analysis in this study was conducted using interview techniques. It was concluded that the services provided by the East Kutai Police SPKT were very good, this can be seen from the results of the respondents' answers who said that officers provide Service: Smile, Greet, Greeting, when providing services, then the service system provided by officers is also according to standards. operating procedure (SOP) and not complicated, apart from that the service period provided is in accordance with applicable regulations, and officers have never asked for fees during the service process or there have been no illegal fees requested by officers, this is proven by the presence of CCTV installed in the SPKT service room, so that if there are complaints regarding illegal levies, the CCTV can be used as evidence, besides that the officers also receive criticism and suggestions, this can be seen from the existence of a suggestion box in the SPKT room